Spectral Analysis of Vowels and Fricatives at Varied Levels of Dysarthria Severity for Amyotrophic Lateral Sclerosis - Thirumala Kumar, Chowdam Venkata; Bhattacharjee, Tanuka; Vengalil, Seena; Nashi, Saraswati; Keerthipriya, Madassu; Belur, Yamini; Nalini, Atchayaram; Ghosh, Prasanta Kumar (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2024)
Dysarthria due to Amyotrophic Lateral Sclerosis (ALS) affects the acoustic characteristics of different speech sounds. The effects intensify with increasing severity leading to the collapse of the acoustic space of the affected individuals. With an aim to characterize such changes in the acoustic space, this paper studies the variations in band-specific and full-band spectral properties of 4 sustained vowels (/a/, /i/, /o/, /u/) and 3 sustained fricatives (/s/, /sh/, /f/) at different dysarthria severity levels. Effect of dysarthria on spectral features of these phonemes are not well explored. Statistical comparison of these features among different severities for the phonemes considered and among different vowels/fricatives for every severity level using speech data from 119 ALS and 40 healthy subjects indicate the followings. Though all band-specific and full-band features of the three fricatives and most of those features for the four vowels become statistically similar at high severity levels, certain features remain distinguishable. Spectral differences in 0-2 kHz band between /a/ and the other vowels and in the 2-6 kHz band between /a/ and /o/, /u/ persist through all severity levels. Moreover, properties of /f/ remain mostly unchanged with increasing dysarthria severity levels.